Disaster Management Approach Based on Hexahelix-Model (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
ABSTRACT: Disaster becomes a serious problem when the inability of various parties to anticipate it. Piles of garbage become one of the important factors that damage the tourism image in Bali. The issue also needs to involve multiple groups of stakeholders. This study aims to analyze collaboration between stakeholders in waste management in Bali based on the Hexa helix model. The method in this research is qualitative with an exploratory approach. The study results showed waste management as a form of disaster mitigation activity. Collaboration in waste management has made room for each component of the Hexa Helix model according to its field and capacity. What strengthens is customary rules as social capital regulating community behavior in waste management. As a recommendation, the Hexa helix model to be more effective and efficient in waste management is expected to be applied at the village level.